Pastoralism in Crisis: Mounting Challenges in Herding System in High Altitude Region of Nepal - Bhusal, Prabin; Banjade, Mani Ram; Paudel, Naya Sharma (Journal of Forest and Livelihood, 2019)
This paper discusses on the mounting livelihoods challenges of high altitude region of Nepal driven largely by the growing conflict between pastoralists and community forestry (CF), and offers alternative pathways. The paper is based on a three-year action research using adaptive learning as an approach to understanding conflicts between the herders and CF members and other challenges around high altitude herding. The paper also brings the case of Suspa- Kshamawati Kalinchowk region with pragmatic issues and concerns that need urgent action. In addition, we analyse information on CF and other pastureland, institutional arrangements of CFUG, analysis of herders’ livelihoods and review of policy process and relevant literature. The research shows that high altitude herding system has been facing several challenges with the conflict between the CF and herders as the main challenge. The conflict with CF has posed extreme threats to the existence of herding system in the region. Similarly, challenges like declining availability and access to quality pasture and hardship, and changing social values has contributed to decreasing herding number in recent years and has also put the unique transhumance livelihood activities in crisis. Finally, implications to policy and practice of CF and overall environmental governance are identified.